Management and pattern of pellet gun injuries in war conflicted Kashmir Valley, India - Mala, Tariq Ahmed; Ahmad, Syeed Rayees; Malla, Shahid Amin (International Journal of Research in Medical Sciences, 2019)
Abstract Background: The pellet gun is a shot gun weapon which is used by law enforcement agencies to maintain law and order in conflict zones whenever need arises. Sometimes these minute sized pellets may lead to grave injuries to vital structures of the body which may sometimes led to permanent disability. The objective of this study was to investigations and manages these fatal injuries in war conflicted valley. Methods: The prospective study conducted in a tertiary care hospital of Government Medical College Srinagar at the time of civilian unrest in 2016 and onwards when thousands of people were injured with pellets by security agencies. Results: Maximum number (67.1%) of patients had injuries to eyes and face, among the total number of patients 69 (17.2%) of patients had abdominal injuries. CECT abdomen showed pellets in all 69 (100%) of patients, pellets in gut lumen in 48 (69.5%) of patients. In the abdominal group 40 patients underwent laparotomy which showed hemoperitoneum in 49 (71.01%), pneumoperitoneum in 6 (8.69%) of patients. Conclusion: Pellet gun weapon has become a common arsenal to suppress the unarmed civilian agitation which may lead to fatal injuries to vital structures of body, where prognosis remained poor despite of best available treatment.